Marijuana Induced Gingival Enlargement - Dhakal, Robins; Chaudhary, Shashi Kant; Singh, Ripu; Sharma, Shivalal; Shrestha, Ashish (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Different aetiologies with various clinical presentations are evident in cases of gingival enlargement. We report a case of 34-year-old male who presented with the chief complaint of gingival overgrowth in upper and lower front teeth region. Patient was systemically healthy and gave no history of common medications known to cause gingival enlargement. He had a history of marijuana consumption for two consecutive years following which gingival swelling increased in severity. Based on clinical and histopathologic findings, provisional diagnosis of combined inflammatory + marijuana induced gingival enlargement was made. Treatment consisted of scaling and root planing followed by sextant wise gingivectomy. Results were stable until three months follow-up. Signs of inflammation were evident when the patient reported after 1.5 years.